A Polythiophene Material Featuring a Conjugated Carbonyl Side Group as an Anode for Lithium‐Ion Batteries. Issue 27 (18th July 2022) - Zhang, Chengjun; Chen, Sha; Zhou, Guangying; Hou, Qiong; Wang, Yuhai; Shi, Guang
Abstract: Converting small organic molecules to their lithium salts or polymerization effectively solves the capacity fading caused by the dissolution of small organic molecules in electrolytes. While polymer lithium salts have the characteristics of small molecular lithium salts and polymers and can obtain good cycle stability and rate performance. The 3‐carboxylithium substituted thiophene (3‐TCOOLi) and polymer (P3‐TCOOLi) anode materials for lithium‐ion batteries were synthesized, and their electrochemical properties were compared. Compared with the small‐molecule lithium salt 3‐TCOOLi electrode, the polymer P3‐TCOOLi electrode exhibits superior cycling and rate performance. The P3‐TCOOLi electrode still has a specific capacity of 390 mAh g −1 after 100 cycles at a current density of 50 mA g −1 . During the rate charge and discharge process, when the current density increased to 1000 mA g −1, the specific capacity was 305 mAh g −1 . It shows that the idea of small molecule lithium salt polymerization is feasible. Abstract : The polymer lithium salt anode material for the lithium‐ion battery has the characteristics of both small molecular lithium salt and polymer, which can obtain good cycle stability and rate performance. Herein we compared the electrochemical performance of a polymer lithium salt and its small‐molecule lithium salt anode materials. Polymer lithium salt exhibits better cycling and rate performance.